Hypertension Self-Management and Stroke Recovery Among Rural Adults in the Stroke Belt: A Mixed-Methods Study - Mudasir Andrabi; Betty Key; Chaitali Dagli; Kayla Glass-Lucena; Stephanie Hart; Susan Appel; Chen Lin; Karlene Ball (Rehabilitation Nursing Journal, 2026)
Purpose: To assess hypertension-related knowledge, self-management behaviors, and post-stroke needs among African American (AA) stroke survivors in rural Alabama. Design: Cross-sectional, mixed-methods study. Methods: Using convenience sampling, we recruited 25 AA stroke survivors aged 50 years or older from three rural counties in Alabama. Quantitative data were collected using the Hypertension Knowledge-Level Scale (HK-LS), hypertension Self-Care Activity Level Effects (H-SCALE), and the Southampton Stroke Self-Management Questionnaire. Fourteen participants completed semi-structured interviews. Descriptive statistics and thematic analysis were used to analyze the data. Results: Most participants had low hypertension knowledge (56%) and poor adherence with medication (76%), the DASH diet (84%), physical activity (56%), and smoking cessation (72%). Qualitative analysis of participant interviews identified key barriers to hypertension management and post-stroke recovery, including limited hypertension knowledge, poor adherence, gaps in continuity of care, and limited social support. Clinical Relevance: Rehabilitation nurses play a critical role in improving hypertension management and post-stroke recovery through culturally tailored education, reinforcement of self-management behaviors, and improved care coordination. Strengthening patient education and access to community-based resources may reduce recurrent stroke risk and improve outcomes. Conclusions: AA stroke survivors in rural settings face significant challenges in hypertension management and recovery. Targeted, culturally responsive, and community-engaged interventions are needed to improve self-management and long-term outcomes.